Multi-Dimensional Wireless Signal Identification Based on Support Vector Machines - Tekbiyik, Kursat; Akbunar, Ozkan; Ekti, Ali Riza; Gorcin, Ali; Kurt, Gunes Karabulut (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
Radio air interface identification provides necessary information for dynamically and efficiently exploiting the wireless radio frequency spectrum. In this study, a general machine learning framework is proposed for Global System for Mobile communications (GSM), Wideband Code Division Multiple Access (WCDMA), and Long Term Evolution (LTE) signal identification by utilizing the outputs of the spectral correlation function (SCF), fast Fourier Transform (FFT), auto-correlation function (ACF), and power spectral density (PSD) as the training inputs for the support vector machines (SVMs). In order to show the robustness and practicality of the proposed method, the performance of the classifier is investigated with respect to different fading channels by using simulation data. Various over-the-air real-world measurements are taken to show that wireless signals can be successfully distinguished from each other without any prior information while accounting for a comprehensive set of parameters such as different kernel types, number of in-phase/quadrature (I/Q) samples, training set size, or signal-to-noise ratio (SNR) values. Furthermore, the performance of the proposed classifier is compared to the existing well-known deep learning (DL) networks. The comparative performance of the proposed method is also quantified by classification confusion matrices and Precision/Recall/F-1-scores. It is shown that the investigated system can be also utilized for spectrum sensing and its performance is also compared with that of cyclostationary feature detection spectrum sensing.
Keywords: Cyclostationarity; FFT; machine learning; power spectral density; spectral correlation function; spectrum sensing; support vector machine; wireless signal identification; AUTOMATIC MODULATION CLASSIFICATION; Computer Science; Engineering; Telecommunications